The imprint of cosmic web quenching on central galaxies - Winkel, Nico; Pasquali, Anna; Kraljic, K.; Smith, R.; Gallazzi, A.; Jackson, Thomas M. (Monthly notices of the Royal Astronomical Society, 2021)
We investigate how cosmic web environment impacts the average properties of central galaxies in the Sloan Digital Sky Survey (SDSS). We analyse how the average specific star formation rate, stellar age, metallicity, and element abundance ratio [α/Fe] of SDSS central galaxies depend on distance from the cosmic web nodes, walls, and filaments identified by the Discrete Persistent Structures Extractor (DisPerSE). In our approach we control for galaxy stellar mass and local density differentiated between field and group environment. Our results confirm the known trend whereby galaxies exhibit lower specific star formation rates with decreasing distance to the cosmic web features. Furthermore, we show that centrals closer to either nodes, walls, or filaments are on average older, metal richer, and α-enhanced compared to their equal mass counterparts at larger distances. The identified property gradients appear to have the same amplitude for central galaxies in the field as for those in groups. Our findings support a cosmic web quenching that stems from nurture effects, such as ram pressure stripping and strangulation, and/or nature effects linked to the intrinsic properties of the cosmic web.